Não é desencanto, é desejo pelo novo: percepções dos jovens em relação à política - Gomes, Victória Kelwia Ferreira (2025)
Politics is often perceived as a sensitive topic in everyday life, often avoided due to its controversial, divisive and controversial nature. Such characteristics tend to polarize people's attitudes, leading them to extremes of engagement or complete apathy. This is especially true among young people, who, as they are in the process of forming their identities and constructing values, tend to present intense and polarized reactions to the political scenario. It is in this context of contrasting reactions that this study is inserted, with the objective of investigating young people's perceptions of politics. The methodological approach adopted was a qualitative one that used two instruments: the application of questionnaires (Survey) and the holding of focus groups, which complemented each other in the investigation of young people's perceptions of politics. The results of this research demonstrated that there is a distancing of young people from politics, but despite this, a contrary fact was also observed to the hegemonic view that had been held about youth regarding young people being alienated, depoliticized, and disinterested. Youth understands the importance of political competition in their lives, and to some extent, they were even interested in participating in politics, but in a different 'politics.' It was also analyzed that this posture of relative disinterest in politics occurs due to different factors, such as disillusionment with politicians and individualism, typical of capitalist societies. Therefore, it can be inferred that politics needs to reinvent itself to contemplate young people and their ideologies as thinking beings who do not dialogue with the traditional way of doing things. Furthermore, more people who understand the reality of the people need to occupy these positions of power, because, in the view of young people, this would generate the change that politics so badly needs and would condition them to participate more actively. Furthermore, schools need to act more effectively and enable these debates to take place in the educational sphere through new theoretical-methodological strategies, in order to provide opportunities for the inclusion of the entire society and, above all, the public addressed in this research, which is the youth.